Population Structure, Molecular Epidemiology, and β-Lactamase Diversity among Stenotrophomonas maltophilia Isolates in the United States - Mojica, Maria F.; Rutter, Joseph D.; Taracila, Magdalena; Abriata, Luciano A.; Fouts, Derrick E.; Papp-Wallace, Krisztina M.; Walsh, Thomas J.; LiPuma, John J.; Vila, Alejandro J.; Bonomo, Robert A. (mBio, 2019)
Multiple antibiotic resistance mechanisms, including two β-lactamases, L1, a metallo-β-lactamase, and L2, a class A cephalosporinase, make S. maltophilia naturally multidrug resistant. Thus, infections caused by S. maltophilia pose a big therapeutic challenge. Our study aims to understand the microbiological and molecular characteristics of S. maltophilia isolates recovered from human sources. A highlight of the resistance profile of this collection is the excellent activity of the ceftazidime-avibactam and aztreonam combination. We hope this result prompts controlled and observational studies to add clinical data on the utility and safety of this therapy. We also identify 35 and 43 novel variants of L1 and L2, respectively, some of which harbor novel substitutions that could potentially affect substrate and/or inhibitor binding. We believe our results provide valuable knowledge to understand the epidemiology of this species and to advance mechanism-based inhibitor design to add to the limited arsenal of antibiotics active against this pathogen. Stenotrophomonas maltophilia is a Gram-negative, nonfermenting, environmental bacillus that is an important cause of nosocomial infections, primarily associated with the respiratory tract in the immunocompromised population. Aiming to understand the population structure, microbiological characteristics and impact of allelic variation on β-lactamase structure and function, we collected 130 clinical isolates from across the United States. Identification of 90 different sequence types (STs), of which 63 are new allelic combinations, demonstrates the high diversity of this species. The majority of the isolates (45%) belong to genomic group 6. We also report excellent activity of the ceftazidime-avibactam and aztreonam combination, especially against strains recovered from blood and respiratory infections for which the susceptibility is higher than the susceptibility to trimethoprim-sulfamethoxazole, considered the “first-line” antibiotic to treat S. maltophilia . Analysis of 73 bla L1 and 116 bla L2 genes identified 35 and 43 novel variants of L1 and L2 β-lactamases, respectively. Investigation of the derived amino acid sequences showed that substitutions are mostly conservative and scattered throughout the protein, preferentially affecting positions that do not compromise enzyme function but that may have an impact on substrate and inhibitor binding. Interestingly, we detected a probable association between a specific type of L1 and L2 and genomic group 6. Taken together, our results provide an overview of the molecular epidemiology of S. maltophilia clinical strains from the United States. In particular, the discovery of new L1 and L2 variants warrants further study to fully understand the relationship between them and the β-lactam resistance phenotype in this pathogen. IMPORTANCE Multiple antibiotic resistance mechanisms, including two β-lactamases, L1, a metallo-β-lactamase, and L2, a class A cephalosporinase, make S. maltophilia naturally multidrug resistant. Thus, infections caused by S. maltophilia pose a big therapeutic challenge. Our study aims to understand the microbiological and molecular characteristics of S. maltophilia isolates recovered from human sources. A highlight of the resistance profile of this collection is the excellent activity of the ceftazidime-avibactam and aztreonam combination. We hope this result prompts controlled and observational studies to add clinical data on the utility and safety of this therapy. We also identify 35 and 43 novel variants of L1 and L2, respectively, some of which harbor novel substitutions that could potentially affect substrate and/or inhibitor binding. We believe our results provide valuable knowledge to understand the epidemiology of this species and to advance mechanism-based inhibitor design to add to the limited arsenal of antibiotics active against this pathogen.